Individual, social, and environmental influences on the transitions in physical activity among emerging adults - Kaigang Li; Danping Liu; Denise Haynie; Benjamin Gee; Ashok Chaurasia; Dong-Chul Seo; Ronald J. Iannotti; Bruce G Simons-Morton (BMC, 2016)
Abstract Background Youth's physical activity (PA) may change across developmental periods. Although previous studies have observed a decline in levels of PA during adolescence, few studies have explored trends in PA during the transition from adolescence to young adulthood and what factors may impact the transitional change. The purpose of this study was to examine changes and predictors of change over time in PA from 10th grade to post-high school. Methods The NEXT Generation Health Study recruited a nationally-representative cohort of US 10th-graders, and administered longitudinal surveys in four waves (years) to follow up the participants to their first year after high school. Using transition models, the self-reported outcomes, moderate-to-vigorous PA (MVPA) and vigorous PA (VPA) each of which was repeatedly measured by one question, were modelled in association with wave-4 environmental-status variables and time-varying covariates. Results There was a continuous decline in the proportion of respondents who met or exceeded the minimum recommended level for either MVPA (from 55.97 to 34.33 %) or VPA (from 65.96 to 54.90 %) from W1 to W4. Higher scores of peer PA, family support and VPA planning were prospectively associated with higher likelihood of meeting the MVPA/VPA recommendations. At wave 4, compared to those not working, attending 4-year colleges, or living on campus, participants working full/part time, not attending school or attending community-college level schools, and living at home or in own place were more likely to engage in MVPA. Conclusions Peer PA, family support, self-regulatory skills, and environmental status after high school are critical factors that can promote MVPA/VPA among adolescents and emerging adults.